Description of the female of Sciopemyia servulolimai (Damasceno & Causey) (Diptera: Psychodidae) - Andrade Filho José Dilermando; Galati Eunice A Bianchi; Sousa Raimundo Nonato de; Falcão Alda Lima (Memorias do Instituto Oswaldo Cruz, 2003)
The female of Sciopemyia servulolimai (Damasceno & Causey), based on three specimens captured during an epidemiological research project in the state of Ceará, Brazil, is described and illustrated for the first time.